Sustainable synthesis of natural deep eutectic solvents (NADES) by different methods - Santana, Ana P.R. [UNESP] (2019)
Natural deep eutectic solvents (NADES) based on malic acid-citric acid-water (MA-CA), xylitol-citric acid-water (Xyl-CA) and xylitol-malic acid-water (Xyl-MA) were prepared according to three different methods: controlled heating and stirring, ultrasound-assisted synthesis (UAS), and microwave-assisted synthesis (MAS), in each case employing a 1:1:10 M ratio. The NADES were characterized by infrared spectroscopy (ATR-FTIR), which indicated the formation of intermolecular interactions such as hydrogen bonds between the precursors, irrespective of the synthesis method. Thermogravimetric analysis (TGA) was used to obtain the thermal decomposition profiles of the synthesized solvents, which evidenced interactions between the precursors and decomposition temperatures higher than 150 °C. Determination of the physical properties showed no significant differences of viscosity and density among the NADES produced using the different synthesis methods, at a 95% confidence level. Hence, all the methods used for the synthesis of NADES resulted in solvents with similar physicochemical characteristics. The syntheses assisted by ultrasound and microwaves were faster and efficient, while advantages of the stirring and heating method included the use of simpler equipment and the ability to produce larger volumes of solvents.